HGG-50. Specific sensitivity of pediatric high-grade glioma with ATRX inactivation to PARP inhibitor combinations. (3rd June 2022) - Laemmerer, Anna; Kirchhofer, Dominik; Madlener, Sibylle; Loetsch-Gojo, Daniela; Jaunecker, Carola N; Gabler, Lisa; Mayr, Lisa; Stepien, Natalia; Baumgartner, Alicia; Dieckmann, Karin; Pfister, Stefan M; Kool, Marcel; et al.
Abstract: Pediatric high-grade gliomas (pHGG) account for approximately 12% of pediatric brain tumors. Despite advances in molecular diagnosis and identification of discrete molecular subtypes, pHGG are the leading cause of cancer-related death in children. Thus, current research focuses on identifying novel therapeutic targets. Sequencing analyses across pediatric cancer types identified DNA repair perturbations as potentially targetable events in certain types of pediatric brain tumors. Herein, we investigated the potential of PARP inhibitors (PARPi), impeding the central role of PARP in DNA damage repair, in pHGG. We screened a patient-derived primary pHGG cell line panel (n=7) for their sensitivity towards 6 different PARPi (niraparib, olaparib, pamiparib, rucaparib, talazoparib, veliparib) using cell viability assays. Basal expression of DNA repair related proteins was assessed by immunoblot, and propidium iodide-based flow cytometry was used for cell cycle analysis. All pHGG were resistant towards single compound PARP inhibition. Interestingly, two H3F3A - G34R mutant pHGG models harboring inactivating ATRX mutations were characterized by elevated basal levels of pH2AX, suggesting increased stress resulting from DNA damage. Consequently, simultaneous targeting of PARP and other components of DNA repair in the respective models showed strong synergistic effects on cell viability, which was not observed to a comparable extent in other models such as BRAFV600E / TERT promotor mutant pHGG. Combination of talazoparib and irinotecan resulted in S-phase arrest. Within a precision oncology approach, we treated a 11-year-old child suffering from H3F3A - G34R mutant pHGG with ATRX mutation, that progressed during radiation, with niraparib and topotecan. The patient achieved partial remission and disease stabilization for 1 year. Taken together, PARPi combinations show potential for the treatment of pHGG with ATRX mutations. Currently, all cell models are characterized for DNA repair signatures by DNA sequencing. Further, in depth characterization of DNA damage responses upon concomitant PARP and topoisomerase inhibition in ATRX -mutated pHGG are ongoing.